2016
DOI: 10.1186/s40659-016-0104-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of a computer-designed potential anticancer agent in cervical cancer cells

Abstract: BackgroundComputer-based technology is becoming increasingly essential in biological research where drug discovery programs start with the identification of suitable drug targets. 2-Methoxyestradiol (2ME2) is a 17β-estradiol metabolite that induces apoptosis in various cancer cell lines including cervical cancer, breast cancer and multiple myeloma. Owing to 2ME2’s poor in vivo bioavailability, our laboratory in silico-designed and subsequently synthesized a novel 2ME2 analogue, 2-ethyl-3-O-sulphamoyl-estra-1,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Furthermore, data from our cell cycle progression studies also revealed that the treatment of both MDA-MB-231 and MCF-7 breast cancer cells to ESE-15-ol alone leads to a significant increase in cells present in the G 2 /M phase. These results were consistent with previous studies from our laboratory which showed that ESE-15-ol caused a marked G 2 /M cell cycle arrest in cervical cancer (HeLa) and breast cancer (MCF-7, MDA-MB-231 and MCF-12A) cell lines [19, 20]. These results indicate that ESE-15-ol is able to induce a mitotic cell cycle arrest.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, data from our cell cycle progression studies also revealed that the treatment of both MDA-MB-231 and MCF-7 breast cancer cells to ESE-15-ol alone leads to a significant increase in cells present in the G 2 /M phase. These results were consistent with previous studies from our laboratory which showed that ESE-15-ol caused a marked G 2 /M cell cycle arrest in cervical cancer (HeLa) and breast cancer (MCF-7, MDA-MB-231 and MCF-12A) cell lines [19, 20]. These results indicate that ESE-15-ol is able to induce a mitotic cell cycle arrest.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies in our laboratory have shown that ESE-15-ol is more potent than 2ME2 and that ESE-15-ol inhibits cell growth of the human tumorigenic breast epithelial cell line (MCF-7), human metastatic breast cell line (MDA-MB-231), human cervical adenocarcinoma cells (HeLa), and human nontumorigenic breast epithelial cell line (MCF-12A) [19, 20]. ESE-15-ol binds to the colchicine binding site on tubulin, thus triggering cells to undergo mitotic arrest which consequently leads to the induction of apoptosis [19, 20]. The MCF-12A cells were the least affected by 50 nM ESE-15-ol when compared to MDA-MB-231 and MCF-7 cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…A stock solution of EMBS dissolved in dimethyl sulphoxide (DMSO) was prepared with a concentration of 10 mM and was stored at 4°C. Previous studies conducted in our laboratory demonstrated optimal antiproliferative activity after exposure to 0.4 μM EMBS for 24 h [ 15 ]. For this reason, for all subsequent experiments, cell lines were exposed to 0.4 μM EMBS.…”
Section: Methodsmentioning
confidence: 99%
“…We showed that EMBS exposure led to mitochondrial membrane depolarisation, caspase 6 and caspase 7 activation, while the extrinsic apoptotic pathway was also activated through caspase 8 [ 14 ]. Furthermore, 2ME2 exposure also resulted in increased reactive oxygen species (ROS) generation including hydrogen peroxide and superoxide [ 2 , 15 ]. 2ME2-dependent ROS induction was also responsible for endoreduplication in nasopharyngeal carcinoma cells via c-Jun N-terminal kinase (JNK) and mitogen-activated protein kinase family (MAPK) activation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation